El lenguaje especulativo de Hegel y San Anselmo en las pruebas de la existencia de Dios (Revista Eletrônica Estudos Hegelianos, 2015)
The entity of God is an essential metaphysical concept that needs speculative language to be known. Hegel understands the flourish of that language is able to prove the Existence of God, in Saint Anselm’s meditations on Divine Essence, Monologium and Proslogium. Both meditations present philosophical reflections using: arguments, conclusions, and proofs, for articulating reasons and truth evidences. Ultimately, the Anselmian meditations about mysteries of faith are directed to elevate the human soul towards the contemplations of the Divinity, and to its first principle as the last subject of the predications of the Cosmos, being God the most perfect being, the first Origin from where the existences of all the other beings stem.